Special breast issues: altered breast due to reduction, cosmetic augmentation and post treatment reconstruction - Hassan, Radhiana (2018)
A lecture on mammographic findings of altered breast due to reduction mammoplasty, cosmetic augmentation of breast of various types and post treatment changes.